The Impact of Indonesia’s Cocoa Downstream Policy on the Derivative Product Competitiveness, Export Specialization, and Farmers Benefits - Fatkurrohim; Fitri, Annisa; Andriyanty, Reny; Agustia, Devi; Hutagaol, Manuntun Parulian; Harianto, Harianto (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2025)
The cocoa downstream policy should be aims to improve the welfare of cocoa farmers, not merely to develop the cocoa downstream industry. This study aims to analyze the impact of Indonesia's cocoa downstream policy through cocoa beans export taxes on the competitiveness and trade performance of cocoa derivative products, as well as its benefits to cocoa farmers. The methods employed include TBI values, RCA index, and product mapping classification. The results show that export taxes have enhanced the export competitiveness of cocoa derivative products such as cocoa paste, butter, and powder, with RCA indices exceeding 1 (comparative advantage) and TBI values approaching 1 (net exporter). Cocoa butter stands out as Indonesia's leading export product, deserving prioritization in export specialization, based on the product mapping classification that consistently place it in Group A. However, the benefits of the export taxes are not significantly felt by cocoa farmers, as the growth in the selling price and planted area of cocoa beans have become more stagnant and tend to decline. The government should evaluate the policy's impact on the welfare of cocoa farmers. The policy should benefit not only the downstream actor (industry) but also upstream actor (cocoa farmers).